Taux de familiarité avec les revues universitaires d’assurance aux États-Unis - Outreville, J. François (Assurances)

(untitled) (HEC Montréal, 1987)
Although strictly oriented to academic journals, the following study by Mr. Outreville is also of interest to insurance theorists. In a period during which the industry is undergoing extensive change, this article will serve as a guide to pinpoint the reading habits of both the insurance theorist and the insurance practitioner.